The Hottest Neptunes Orbit Metal-rich Stars - Shreyas Vissapragada; Aida Behmard (The Astronomical Journal)
The Neptune desert is no longer empty. A handful of close-in planets with masses between those of Neptune and Saturn have now been discovered, and their puzzling properties have inspired a number of interesting theories on the formation and evolution of desert-dwellers. While some studies suggest that Neptune desert planets form and evolve similarly to longer-period Neptunes, others argue that they are products of rare collisions between smaller planets, or that they are the exposed interiors of giant planets (i.e., “hot Jupiters gone wrong”). These origin stories make different predictions for the metallicities of Neptune desert host stars. In this paper, we use the homogeneous catalog of stellar metallicities from Gaia Data Release 3 to investigate the origins of Neptune desert dwellers. We find that planets in the Neptune desert orbit stars that are significantly more metal rich than the hosts of longer-period Neptunes ( p = 0.0016) and smaller planets ( p = 0.00014). In contrast, Neptune desert host star metallicities are statistically indistinguishable from those of hot Jupiter host stars ( p = 0.55). Therefore, we find it relatively unlikely that Neptune desert planets formed and evolved similarly to longer-period Neptunes, or that they resulted from collisions between smaller planets, at least without another metallicity-selective process involved. A more straightforward explanation for this result is that planets in the desert truly are the exposed interiors of larger planets. Atmospheric spectroscopy of Neptune desert worlds may therefore provide a rare glimpse into the interiors of giant exoplanets.